100% - Pope, Paul (DC Comics/ Vertigo, 2009)
100% juggles three separate but interconnected stories that revolve around a downtown Manhattan nightclub catering to demimonde habitues including artists, erotic dancers (whose internal organs are projected onto viewscreens for the ultimate voyeuristic kick), prizefighters, barmaids, and busboys.